The Advocacy Role of the Perioperative Nurse - Thomas-Aasen, Loretta (Operating Room Nurses Association of Canada Journal, 1993)
In 1903 Leila Woodbury made it know to her peers that the “good nurse” was one who informed her patient about the surgical ordeal and supported the patient as an individual. These functions are widely recognized in the contemporary view of the patient advocate.‘ The advocacy role evolved from a critical examination of the ideological base, values, and concepts of perioperative nursing. The role has changed from the concept of skilled manipulation of equipment and supplies to that of preventing illness and maintaining the patient’s health status.‘